Touristic destination selection in accommodation business investment decision: Entropy-TOPSIS integrated approach - Göral, Ramazan (Journal of Tourism Management Research, 2025)
Choosing the right location is crucial for the success of a business. Selecting an inappropriate site for accommodation investments can adversely impact the business and potentially lead to failure. Therefore, it is essential to determine the most suitable location through an objective and systematic approach. This research proposes a methodology that combines entropy-based weighting and TOPSIS multi-criteria decision-making (MCDM) methods to support the tourism destination selection process in investment decisions. The study analyzed 19 tourism destinations in Turkey that hosted 100,000 or more foreign tourists, according to the Ministry of Culture and Tourism’s 2024 Border Statistics Annual Bulletin. The evaluation criteria included distance to the nearest airport (in kilometers), population, Herfindahl Index Contribution Level, hotel occupancy rate, number of tourists (demand), and seasonality. Criterion weights were calculated using the entropy method, and destination rankings were established using the TOPSIS method. The reliability of the findings was validated through Spearman’s Rank Correlation analysis. Additionally, the robustness of the results was confirmed via Monte Carlo sensitivity analysis. The analysis revealed that Istanbul and Antalya are the most attractive destinations for accommodation investments. Conversely, cities with smaller populations and limited tourism activities, such as Ardahan, Iğdır, and Hakkari, ranked lower. The methodology employed in this study is expected to aid investors and policymakers in evaluating tourism destinations effectively.